Electronic Instrumentation and Measurements - David A. Bell (New Delhi, Oxford University Press, 2023)
Electronic Instrumentation and Measurements is designed as a textbook for undergraduate students of electrical, electronics and instrumentation disciplines. It presents a comprehensive treatment of the operation, performance, applications and limitations of both digital and analog instruments, normally encountered in an electronics laboratory. Starting with SI units and measurement errors, the text covers electromechanical instruments, analog electronic instruments, digital voltmeters, frequency meters and resistance, inductance and capacitance measurement techniques. The specialized instruments investigated in the latter half of the book include analog oscilloscopes, digital storage oscilloscopes, signal generators, waveform analyzers and graphic recording instruments. Instrument calibration is also discussed as well as power and energy measurement. To make the text comprehensive, dedicated chapters on magnetic measurements, transducers and telemetry have been included.
Keywords: Electronic Instrumentation And Measurements I Electronics and Communication Engineering